2013
DOI: 10.1242/jcs.121814
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide-co-glycolide-rifampicin-nanoparticles efficiently clearMycobacterium bovisBCG infection in macrophages and remain membrane-bound in phago-lysosomes

Abstract: Summary Nanoparticles (NPs) are increasingly used as biodegradable vehicles to selectively deliver therapeutic agents such as drugs or antigens to cells. The most widely used vehicle for this purpose is based on copolymers of lactic acid and glycolic acid (PLGA) and has been extensively used in experiments aimed at delivering antibiotics against Mycobacterium tuberculosis in animal models of tuberculosis. Here, we describe fabrication of PLGA NPs containing either a high concentration of rifampicin or detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 53 publications
9
81
0
Order By: Relevance
“…More groups supported this interpretation for different cell types, including macrophages [41][42][43]. On the other hand, the PLGA particles were suggested to remain within the phagolysosomal compartment for several days [44][45][46]. Another issue is the ability for PLGA particles to reach the compartment in which mycobacteria reside.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…More groups supported this interpretation for different cell types, including macrophages [41][42][43]. On the other hand, the PLGA particles were suggested to remain within the phagolysosomal compartment for several days [44][45][46]. Another issue is the ability for PLGA particles to reach the compartment in which mycobacteria reside.…”
Section: Introductionmentioning
confidence: 97%
“…Another issue is the ability for PLGA particles to reach the compartment in which mycobacteria reside. One group suggested this possibility [47], but others could not demonstrate it [10,45].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using BCG-infected mice models, Griffith et al demonstrated the differential localization of BCG and PLGA nanoparticles within mouse primary macrophages. [37] When infecting macrophages, BCG predominantly resided within phagosomes. However, when drug-loaded PLGA nanoparticles were phagocytosed by macrophages, they instead localized to the phagolysosome (Figure 7).…”
Section: Polymer Nanoparticles As Anti-tb Drug Delivery Carriersmentioning
confidence: 99%
“…PLGA-RIF NPs were prepared by single water-inoil-in-water emulsion solvent evaporation method and characterized by electron microscopy as described by Kalluru et al (2013).…”
Section: Plga Np and Nlc Preparationmentioning
confidence: 99%